Composting of Protein Waste Using Effective Microorganism by Anaerobic Process - Abdul Rahman, Abdul Muiz Fahmy; Ahmad Nazri, Ahmad Adib Firdaus; Ab Sofi , Afiq Afzal; Nor Farah Atiqah Ahmad (Multidisciplinary Applied Research and Innovation, 2024)
Compost is a mixture of ingredients used as plant fertilizer and to improve soil’s physical, chemical, and biological properties. It is commonly prepared by decomposing plants, food waste, and recycling organic materials and manure. Compost enhances the nutrient content, moisture retention, and soil structure. This study is about to investigate the composting of two types of protein waste (fish and chicken) using effective microorganisms by the anaerobic process which later used as organic fertilizer. The comparison of two type of fertilizers; fish- and chicken fertilizer were surveyed by the growth of Okra plant for 28 days. Based on the property test, fish fertilizer has higher pH, temperature and ammonia nitrogen content; 6.8 pH, 55ºC and 155mg/L. This helped in boosting the Okra plant growth as the height increase by 4.6% each week compared to chicken fertilizer with increasing of 2.5%. It is particularly important for the development of healthy stems, leaves, and foliage. This research can make it easier to comprehend how compost can improve plant health overall, inhibit disease, and increase crop output.